Sensitive Organophosphorus and Carbamate Pesticides Biosensor Based on Acetylcholinesterase and CdZnSe/ZnS Ternary Alloy Quantum Dots - Hai, Nguyen Ngoc; Yen, Nguyen Hai; Giang, Duong Thi; Nhat, Nguyen Duc; Nga, Pham Thu; Cao, Dao Tran (Communications in Physics, 2014)
This report presents the results of ternary alloy quantum dots (TQDs) manufacturing and its superior optical properties to fabricate the biosensor for pesticide detection. The explanation for the changes in PL intensity based on the change of electronic charges that alters the pH value of the surrounding environment, and the types of interaction on the surface of CdZnSe/ZnS TQDs were discussed. We show the decomposition process of the indicator (ATCh) with the catalysis from acetylcholinesterase enzyme (AChE) that inhibited by organophosphorus and carbamate pesticides including Trichlorfon (TF), Cypermethrin (CH), Abamectin (AT), and Carbosulfan (CS) with concentrations from 0.05 ppm to 10 ppm.